Forecast scenarios on the socio-economic conditions of small-scale fishers in the coastal towns of the first district of Zamboanga del Norte - Naguit, Maria Rio A.; Campiseño, Evelyn R.; Malate, Renato F.; Lopez, Ana Liza (2012)
This paper describes the socioeconomic conditions of the small-scale fishers in the coastal towns of the first district of Zamboanga del Norte and attempts to describe their future conditions via scenario analysis (up to year 2020). Posteriori probability estimates show that the most likely scenario for the fishers in these municipalities is that they will remain poor and poorly educated so that their numbers would increase (for lack of alternative livelihood) and poverty incidence will significantly rise as well. Intervention through higher and technical education of the relatively young household members are needed to forestall the occurrence of the likely scenario in 2020.
Keywords: Small-scale fishers; Fishers -- Zamboanga del Norte; Mindanao studies; Fishers -- Literary collections